The importance of infill drilling in a mature offshore field - Ismail, Issham (Faculty of Chemical & Natural Resources Engineering, 1991)
Infill drilling is commonly used in a mature offshore field to achieve accelerated production and improved recovery. Generally, infill drilling can improve oil recovery via sweeping unswept zones, and also by improving areal and vertical sweep, thus will improve the economic limit.